Ability of a Wild Weissella Strain to Modify Viscosity of Fermented Milk - Bancalari, Elena; Alinovi, Marcello; Bottari, Benedetta; Caligiani, Augusta; Mucchetti, Germano; Gatti, Monica (Frontiers in Microbiology, 2020)
Despite strains belonging to Weissella species have not yet been approved for use as starter culture, recent toxicological studies open new perspectives on their potential employment. The aim of this study was to evaluate the ability of a wild Weissella minor (W4451) strain to modify milk viscosity compared to Lactobacillus delbrueckii subsp. bulgaricus which is commonly used for this purpose in dairy products. To reach this goal, milk viscosity has been evaluated by means of two very different instruments: one rotational viscometer and the Ford-cup. Moreover, water holding capacity was evaluated. W4451, previously isolated from sourdough, was able to acidify milk, to produce polysaccharides in situ and thus improve milk viscosity. The ability of W4451 to produce at the same time lactic acid and high amounts of polysaccharides, makes it a good candidate to improve the composition of starters for dairy products. Ford Cup turned out to be a simple method to measure fermented milk viscosity by small or medium sized dairies.